On the data acquisition, image reconstruction, cone beam artifacts, and their suppression in axial MDCT and CBCT – A review. Issue 9 (6th August 2018) - Tang, Xiangyang; Krupinski, Elizabeth A.; Xie, Huiqiao; Stillman, Arthur E.
Abstract : Purpose: In the clinic, computed tomography (CT) has evolved into an essential modality for diagnostic imaging by multidetector row CT (MDCT) and image guided intervention by cone beam CT (CBCT). Recognizing the increasing importance of axial MDCT/CBCT in clinical and preclinical applications, and the existence of CB artifacts in MDCT/CBCT images, we provide a review of CB artifacts' root causes, rendering mechanisms and morphology, and possible solutions for elimination and/or reduction of the artifacts. Methods: By examining the null space in Radon and Fourier domain, the root cause of CB artifacts (i.e., data insufficiency) in axial MDCT/CBCT is analytically investigated, followed by a review of the data sufficiency conditions and the "circle +" source trajectories. The rendering mechanisms and morphology of CB artifacts in axial MDCT/CBCT and their special cases (e.g., half/short scan and full scan with latitudinally displaced detector) are then analyzed, followed by a survey of the potential solutions to suppress the artifacts. The phenomenon of imaged zone indention and its variation over FBP, BPF/DBPF, two‐pass and iterative CB reconstruction algorithms and/or schemes are discussed in detail. Results: An interdomain examination of the null space provides an insightful understanding of the root cause of CB artifacts in axial MDCT/CBCT. The decomposition of CB artifacts rendering mechanisms facilitates understanding of the artifacts' behavior under different conditions and the potential solutions to suppress them. An inspection of the imaged zone intention phenomenon provides guidance on the design and implementation of CB image reconstruction algorithms and schemes for CB artifacts suppression in axial MDCT/CBCT. Conclusions: With increasing importance of axial MDCT/CBCT in clinical and preclinical applications, this review article can update the community with in‐depth information and clarification on the latest progress in dealing with CB artifacts and thus increase clinical/preclinical confidence.